RECOMBINANT PROTEIN OF VARIOLA VIRUS ABOLISHES THE EFFECTS OF TUMOR NECROSIS FACTOR UPON MARROW HEMATOPOIESIS IN BALB/С MICE - L. B. Toporkova; A. A. Petuhova; I. P. Gileva; I. A. Orlovskaya (Медицинская иммунология, 2014)
We studied the effect of a recombinant murine TNF (rmTNF) and TNF-binding protein of Variola virus (VARV-CrmB) upon colony-forming ability of bone marrow cells (BMC) from Balb/c mice. BMC were grown in semisolid methylcellulose medium supplemented with murine growth factors in the absence or presence of mrTNF along at concentrations ranging from 2 to 40 ng/ml, VARV-CrmB (2 to 24 ng/ml), as well as in presence of both mrTNF (2 ng/ml) and VARV-CrmB (2 to 12 ng/ml). Hematopoietic colonies (BFU-E, CFU-E, and CFU-GM) were scored on day 14. VARV-CrmB protein didn't influence clonogenicity of the bone marrow progenitors. rmTNF inhibited growth of erythroid cells (BFU-E+CFU-E) at all concentrations tested, and stimulated growth of granulocyte-macrophage progenitors (CFU-GM) at concentrations of 2 ng/ml and 10 ng/ml. Combined effect of rmTNF and VARV-CrmB resulted into abolition of rmTNF-induced reduction of BFU-E+CFU-E formation and rmTNF-induced increase of CFU-GM number up to basic levels. Thеse results clearly demonstrate the anti-TNF activity of recombinant viral VARV-CrmB protein.